Implantation of ArtificialIris, a CustomFlex irisprosthesis, in a trauma patient with an Artisan lens: A case report and review. Issue 45 (November 2017) - Doroodgar, Farideh; Jabbarvand, Mahmoud; Niazi, Feizollah; Niazi, Sana; Sanginabadi, Azad
Abstract: Purpose: To evaluate probable complications of Artificial Iris implantation with iris fixated intraocular lens. Method: Development of photophobia, glare, and psychological strain during face-to-face communication in a 23-year-old man with a widespread traumatic iris defect terminate to make a decision for performing implantation of an Artificial Iris (Humanoptics, Erlangen, Germany) under the remnant iris without removing the patient's existing Artisan lens. Results: Without any intraoperative or postoperative complications, the patient's visual acuity increased by 1 line, the endothelial cell loss was comparable with the cell loss associated with standard cataract surgery, and the anterior-chamber depth and anterior-chamber anatomy did not change. At the final follow-up examination, the mean intraocular pressure did not differ from baseline, and we achieved high level of patient satisfaction and subjective vision improvement. We discuss the particular importance of considering the patient's expectations, the appropriate measurements, ways to perfect color evaluation, and the types of Artificial Iris products. Conclusion: The implantation of the Artificial Iris in patients with aphakic iris-supported lenses (ie, pre-existing Artisan lenses) is a feasible approach and a useful option for patients with thin irises and iris hypoplasia who are at risk of subluxation or the dislocation of the posterior-chamber intraocular lens (PCIOL), and also those with sclerally fixed PCIOLs.